Asymmetrical Equivalence Classification – Cluster Affrication vs. Lenis Stops in the Speech of Polish Learners of English - Schwartz, Geoffrey; Wojtkowiak, Ewelina (Research in Language, 2024)
According to the Speech Learning Model (Flege 1995), successful L2 phonological acquisition is facilitated by the formation of new phonetic categories in the L2. However, category formation may be hindered by equivalence classification, wherein speakers perceptually merge L1 and L2 sounds. This study examines L1 Polish learners of English, including a phonetic parameter that has received minimal attention: affrication of /tr-dr/ clusters in English. Two groups of speakers, comprising B1 level and C2 level learners, produced word lists containing both initial /tr-dr/ clusters, as well as singleton voiced stops /b, d, g/. The results revealed an asymmetry: both groups failed to suppress pre-voicing in /b, d, g/, but were successful in producing affricated clusters. A new category has therefore been formed for the clusters, but not for the singleton stops. Phonological implications of this finding are discussed.